Denga pri slovenskih popotnikih po vrnitvi iz tropskih krajev - Kšela, Juš (Medicinski razgledi, 2003)
Dengue fever has reemerged in the past 20 years and expanded to new geographicregions. Together with its causative agents (dengue viruses) and thevectors (Aedes mosquitoes), the epidemic activity and incidence of dengue hemorrhagic fever have been on the increase. With an estimated 100 million cases of dengue fever, 500,000 cases of dengue hemorrhagic fever and 25,000 deaths annually, this mosquito-borne disease is the most important tropical infectious disease after malaria. This paper reviews the epidemiology, history, clinical signs and laboratory characteristics of four dengue fever cases in travelers returning from the tropics, who were hospitalized at the University Hospital, Ljubljana, in the last four years. It is important to educate travelers about the risk of dengue fever before they travel to endemicareas.
Keywords: Denga, virus; Dengue; Diagnosis; Potovanje; Therapy; Tropska klima; Travel; Bolezen, vektorji; Tropical Climate; Odrasli; Dengue Virus; virusne bolezni; Adult; potovanja; Aedes; Virology; Disease Vectors; Denga